1987
DOI: 10.1080/03637758709390233
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of sex differences in marital communication

Abstract: Despite the persistence of sex-typed images of the expressivity of wife and husband, past observational studies have given little indication of sex-linked differences in marital communication. Thus, we proposed that inter personally negotiated role expectations would be a better predictor of communication about marital conflict than sex. However, we also proposed that there might be sex differences within particular clusters of couples who endorse sex-differentiated role expectations. Couples were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…To make the interactions as natural as possible, the couples were asked to complete the conversations alone in their homes. A similar procedure has been used in several studies focusing on marital communication (e.g., Burggraf & Sillars, 1987;Fitzpatrick, Fallis, & Vance, 1982;Pike & Sillars, 1985;Sillars, Pike jones, & Redmon, 1983;ZieÜow & Sillars, 1988), and prior researchers have reported that it yields reliable and valid data. This technique was desirable because even the most comfortable laboratory is prone to have constraints not found in the home (Margolin, Burman, &John, 1989).…”
Section: Completion Of the Conversationsmentioning
confidence: 92%
“…To make the interactions as natural as possible, the couples were asked to complete the conversations alone in their homes. A similar procedure has been used in several studies focusing on marital communication (e.g., Burggraf & Sillars, 1987;Fitzpatrick, Fallis, & Vance, 1982;Pike & Sillars, 1985;Sillars, Pike jones, & Redmon, 1983;ZieÜow & Sillars, 1988), and prior researchers have reported that it yields reliable and valid data. This technique was desirable because even the most comfortable laboratory is prone to have constraints not found in the home (Margolin, Burman, &John, 1989).…”
Section: Completion Of the Conversationsmentioning
confidence: 92%
“…Even if the other person in the conflict has not had the benefit of training, we know that in conflict dyads, people tend to reciprocate behaviors (Burggraf & Sillars, 1987;Deutsch, 2000). Colleagues who, in a conflict, feel listened to and understood, are more likely to extend those behaviors back (Sillars, Wilmot, & Hocker, 1993).…”
Section: Future Directionsmentioning
confidence: 98%
“…Scholars representing a diverse set of theoretical, disciplinary, and methodological commitments have concluded that communication is the primary means by which relationships are maintained, particularly within a marital context (e.g., Canary & Stafford, 1994;Duck, 1994;Gottman & Carrerre, 1994;Wood, 1995). Relationship maintenance refers to the process of sustaining desired relational definitions (Canary & Stafford, 1994).…”
mentioning
confidence: 98%
“…Relationship maintenance refers to the process of sustaining desired relational definitions (Canary & Stafford, 1994). Thus far, signifiMarianne Dainton (Ph.D., Ohio State University, 1994) is Associate Professor of Communication at La Salle University, Philadelphia, PA 19141.…”
mentioning
confidence: 99%